DUKUNGAN SUAMI BERPENGARUH TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III - Septy Ariani Ariani; Evi Rufaidah Evi; Dea Amelia Herdian Dea (Bina Generasi : Jurnal Kesehatan, 2022)
Anxiety is a feeling of restlessness, nervousness or anxiety about something with uncertain outcome that may accompany, influence or cause depression. Anxiety will have a negative impact on pregnant women starting from pregnancy, childbirth and the fetus. At the time of delivery can cause weakened uterine contractions, in the fetus can cause growth retardation. These effects can be harmful to both mother and fetus. This is due to poor family support for pregnant women, one of which is the husband. It is necessary to have husband's assistance in dealing with childbirth to overcome anxiety in the third trimester. With the husband's assistance given to the mother-to-be, the mother feels calmer and has a strong mentality to face childbirth. This study aims to determine the effect of husband's support on anxiety levels in third trimester pregnant women. The research method used is quantitative using a cross sectional design with a population of 106 pregnant women and a sample of 84 respondents. The results showed that the respondents who had insufficient family support were 22 (26.2%) and experienced anxiety disorders as many as 20 respondents, pregnant women who had sufficient family support were 39 (46.4%) respondents and experienced anxiety disorders as many as 38 respondents, while respondents who have good family support are 23 respondents (27.4%) and have anxiety disorders as many as 19 respondents with p value <0.05, which is 0.03. It can be concluded that husband's support can affect the third trimester pregnancy anxiety.